The evolution of a single droplet water-in-palm oil derived biodiesel emulsion leading to micro-explosion - Syed Masharuddin, S.M. (Elsevier B.V., 2022)
Palm oil methyl ester is blended with diesel oil as a commercial diesel product in Malaysia, known as biodiesel B10. Biodiesel mixed with water proved to reduced simultaneously both the particulate matter and NOx during combustion. Emulsified biodiesel also caused a secondary atomization due to micro-explosion of the fuel droplets, which is beneficial in improving combustion efficiency. The main factors and events leading to micro-explosion for palm oil derived biodiesel emulsified fuel has yet to be made available in the open literature. Hence, this study aimed to visualize the droplet evolution to micro-explosion of single droplet when heated. A single droplet was placed on the hot surface of a hotplate maintained at 500 Â°C and the droplet evolution time leading to micro-explosion were capture using a high-speed camera. The study found that all samples of the emulsified fuels produced micro-explosions in four distinct stages. The droplet underwent from a homogenous emulsion, turning from milky color to being transparent during the separation stage, volume expansion during the bubble growth stage, intense coalescence and puffing stage and finally micro-explosion stage. Larger water particles size and higher hydrophilic-lipophilic balance values are the main factors that caused shorter time leading to micro-explosion of droplets. Â© 2021 THE AUTHORS